GENDER STEREOTYPES IN THE 5TH GRADE MATHEMATICS TEACHING MATERIALS - Grigaliuniene, Monika; Kačinskaitė, Roma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Gender equality remains one of the most relevant and therefore most often discussed research subjects. Women's rights and opportunities for self-realization have expanded significantly in recent decades; however, gender discrimination is still encountered in nowadays culture. Various studies show stereotype threat as being one of the undeniable factors for shaping stereotype-based worldview. It is proven that any representation of gender in purely traditional roles not only shapes students’ understanding of abilities and interests of their gender but also has a negative impact on tests' results of a negatively stereotyped group. The object of this study is to evaluate the content of mathematics teaching material used in Lithuanian high schools, and the aim is to investigate the manifestations of stereotyping threats in educational books with qualitative content analysis using an author’s evaluation matrix. The article presents results that reflect stereotype threat in mathematics teaching materials for Lithuanian fifth grade students.